How CCDA instrument analyzed science pre-service teachers’ prior knowledge? - Safira Permata Dewi; E Ermayanti; Lucia Maria Santoso (Biosfer: Jurnal Pendidikan Biologi, 2021)
Increasing the effectiveness of learning is done by exploring the initial understanding of science teacher candidates for the concept of cells to be studied. Exploring the prior knowledge of science teacher candidates about cell concepts can be done using the Cell Cognitive Diagnostic Assessment (CCDA) instrument.This study aims to determine the effectiveness of the CCDA instrument that has been developed. The research sample (n = 163) was student science teacher candidates coming from the Department of Chemistry Education, Physics Education, and Biology Education, Faculty Teaching Training and Education, Sriwijaya University, Indonesia. The topics tested include the structure and function of cells, cell membranes and molecular transport, cell reproduction, and cell communication. The results showed that all the items developed were valid, with a high level of reliability (0.86), very good discrimination index (0.44), and a balance was found between the number of questions classified as difficult and moderate. Although the research results show that this instrument has been valid and reliable, it still needs to be improved on the items so that they can be used in the future.